2015
DOI: 10.1186/s13643-015-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of ward closure to control outbreaks among hospitalized patients in acute care settings: a systematic review

Abstract: BackgroundThough often used to control outbreaks, the efficacy of ward closure is unclear. This systematic review sought to identify studies defining and describing ward closure in outbreak control and to determine impact of ward closure as an intervention on outbreak containment.MethodsWe searched these databases with no language restrictions: MEDLINE, 1946 to 7 July 2014; EMBASE, 1974 to 7 July 2014; CINAHL, 1937 to 8 July 2014; and Cochrane Database of Systematic Reviews, 2005 to May 2014. We also searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Historically, ward closures have been employed to curtail the spread of disease, thereby shortening the overall duration of an outbreak. In recent years, the value and efficacy of applying ward closure to control hospital-acquired infection outbreaks has been questioned because it is one of the most expensive and disruptive IPC measures that can be used [25].…”
Section: Special Measures For Outbreak Control Ward Closurementioning
confidence: 99%
See 1 more Smart Citation
“…Historically, ward closures have been employed to curtail the spread of disease, thereby shortening the overall duration of an outbreak. In recent years, the value and efficacy of applying ward closure to control hospital-acquired infection outbreaks has been questioned because it is one of the most expensive and disruptive IPC measures that can be used [25].…”
Section: Special Measures For Outbreak Control Ward Closurementioning
confidence: 99%
“…Often ward closure is not an option owing to continuous demand for overcapacity, or protocols that govern full capacity because of large patient volumes. It was established that ward closure may not be necessary, depending on the setting and the type of microorganism associated with the outbreak, in recent studies in which the efficiency of ward closure was compared with other, less expensive and less disruptive outbreak methods [25]. Thus, ward closure is considered to be last resort in the control infectious disease outbreaks.…”
Section: Special Measures For Outbreak Control Ward Closurementioning
confidence: 99%
“…In this review, we assess the feasibility of WGS technologies and bioinformatics analysis tools for nosocomial outbreak analyses and provide a comparison to conventional outbreak analysis workflows. Moreover, we review advantages and limitations of sequencing technologies and analysis tools and present INTRODUCTION W hile several improvements have been made to limit the burden of health care-associated infections, outbreaks of especially-multidrug-resistant (MDR) bacteria still present a frequent threat to vulnerable patient populations in hospitals around the world (1). The EPIC II study, which assessed outcomes and prevalences of infections in 13,796 intensive care unit (ICU) patients worldwide, reported that 36% of ICU patients were infected with MDR bacteria, eventually leading to a doubling of their mortality rate compared to uninfected ICU patients (2).…”
mentioning
confidence: 99%
“…Ideally, the decisions to close a ward should consider all foreseeable risks and benefits of each approach. 16 An overall risk assessment is required, including the risk posed for patients already in the HAI outbreak zone, newly admitted patients to this area as well as leaving patients in an ED for prolonged periods of time, and admitting patients to units without specialized services or transferring patients to an outside facility.…”
Section: Discussionmentioning
confidence: 99%
“…The first part of this work has been published as a systematic review. 10 The present work is a survey-based environmental scan that was designed to gain a better understanding of the current practices regarding the use of ward closure to control HAI outbreaks in acute care settings in Canada. The objective of the environmental scan was to determine the frequency of use of ward closure in different acute care hospital settings to control HAI outbreaks; determine the context, triggers, and conditions for the use of ward closure; and provide insight on the professional perspectives and rationale used by hospital administrators, IPC directors, and other infection preventionists (IPs) regarding whether and under what circumstances ward closure is an appropriate means of assisting or aiding in the control of HAI outbreaks.…”
mentioning
confidence: 99%